2014
DOI: 10.1155/2014/174870
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevention Services and Testing Utilization Behaviors among Men Who Have Sex with Men at Elevated Risk for HIV in Chongqing, China

Abstract: Objective. To investigate barriers and correlates of the use of HIV prevention services and HIV testing behaviors among men who have sex with men in Chongqing. Methods. Three consecutive cross-sectional surveys provided demographic, sexual behavior, HIV/syphilis infection, HIV prevention service, and testing behavior data. Results. Of 1239 participants, 15.4% were infected with HIV, incidence was 12.3 per 100 persons/year (95% CI: 9.2–15.3), 38% of the participants reported ever having unprotected insertive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(55 reference statements)
2
10
0
Order By: Relevance
“…Consistent with findings in previous studies, 23 , 24 our research also indicated that MSM with a larger social network (knowing at least 10 MSM in Beijing) were more likely to have accessed HIV testing and other prevention services. In theory, individuals with larger social networks would be more likely to be informed about prevention services.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with findings in previous studies, 23 , 24 our research also indicated that MSM with a larger social network (knowing at least 10 MSM in Beijing) were more likely to have accessed HIV testing and other prevention services. In theory, individuals with larger social networks would be more likely to be informed about prevention services.…”
Section: Discussionsupporting
confidence: 91%
“…Establishment of integrated gay-friendly clinics for comprehensive testing, treatment and prevention for both HIV and STIs is an important step for tackling issues of high incidence of co-infections. Previous studies also showed that MSM sometimes did not seek treatment for their STIs [ 52 , 53 ]. Clinicians should be made aware that there is a high chance to detect new co-infected HIV/syphilis/HSV-2 cases among those with mono-infection of such STIs.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that approximately half of MSM had never been tested for HIV during their lifetime. That rate is higher than those in Beijing and Chongqing where one-third of MSM have never been tested for HIV [ 35 , 36 ]. Further, we reported that 47 % of the participants were not exposed to any HIV intervention measures.…”
Section: Discussionmentioning
confidence: 99%